Discursive tensions in collaboration: stories of the marketplace - Ellis, Nick (International journal of sociology and social policy, 2008)
Purpose - If stories can create promising practices, what does talk of "collaboration" mean in the context of what would appear to be market-based inter-firm relationships (IFRs)? How do managers trying to cope in industrial sectors make sense of supply chain relationships? This empirically driven paper attempts to shed some light on these issues.Design methodology approach - The stories collected here show how a subtle analysis of actors' "network theories" revealed within the language of IFRs can facilitate the study of collaboration. Discourse analysis of interview material is used to illustrate how managers draw upon a series of interpretive repertoires in order to make sense of IFRs within three contrasting "supply chains" or "marketing channels".Findings - Managerial accounts, often in the form of "micro-stories", illustrate how these participants argue persuasively for a "landscape" of next possible actions. This is a landscape that, despite being moulded in part by ideas of network partnerships and "relationship marketing", is more strongly shaped by notions of chains and marketplaces. The paper argues that the discursively constructed network theories of managers constrain their thoughts and actions as they attempt to manage relationships in supply chain contexts. Ultimately, participants appear to forego the opportunities promised by collaborative partnerships; instead their accounts suggest that they retain a world-view dominated by a competitive market orientation.Originality value - Studies that reflect a better understanding of such stories of the marketplace may enable researchers to disseminate findings that help practitioners make more sense of the tensions inherent in inter-firm collaborations.